Keynes, Beveridge and beyond - Cutler, Antony, 1947- (Routledge library editions. Economics series., 2003)
Presenting a coherent interpretation of the development of economic and social policy in Britain since 1945, this book analyses the political assumptions underlying post-war economic policy. It traces these assumptions through the classic texts of Keynes and Beveridge, the architects of limited, non-socialist state intervention to secure the welfare state and full employment. Topics covered include:* 'Private saving' versus company pensions* The level and composition of employment in Britain.